Development and Validation of a Rapid Derivative Spectrophotometric Method for Determination of Tropicamide in Eye Drops: Determination of tropicamide in eye drops - Effat Souri; Massoud Amanlou; Shiva Shahbazi; Mitra Bayat (Iranian Journal of Pharmaceutical Sciences, 2010)
Tropicamide is an antimuscarinic agent used as eye drops for refractive examinations. The aim of this study was to develop a simple and suitable analytical method for determination of tropicamide in eye drops in the presence of excipients. A zero-crossing third and fourth derivative spectrophotometric method was described for determination of tropicamide in eye drops. The measurements were carried out at wavelengths of 263.8 and 255.4 nm for third- and fourth-derivative, respectively. The method was found to be linear (r2> 0.999) in the range of 10-100 µg/ml for tropicamide in the presence of excipients. The limit of determination was 10 mg/ml for tropicamide. The method was successfully applied for determination of tropicamide in eye drops without any interference from excipients or need to prior separation before analysis.